1999
DOI: 10.1111/1469-7610.00426
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging in the Developmental Disorders: The State of the Science

Abstract: The developmental disorders of childhood autistic, developmental language, reading (dyslexia), and attention deficit-hyperactivity disorders-manifest with deficits in the traditional behavioral domains of cognition, language, visual-spatial function, attention, and socialization. However, none of these disorders has been associated with characteristic discrete focal lesions or recognized encephaloclastic processes. Developmental cognitive neuroscientists must therefore begin with the spectrum of sometimes dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(30 citation statements)
references
References 104 publications
1
29
0
Order By: Relevance
“…The predominantly negative findings on tests of the PFC hypothesis are consistent with other research showing only subtle anatomical differences between the frontal lobes of individuals with autism compared with controls (Filipek, 1999); and also with research indicating that some but by no means all executive functions are impaired, at least in people with HFA (Hughes, 2001). The neuropsychological origins of the impaired creativity/behavioural flexibility, which is diagnostic of autism, and the neuropathology underlying the critical neuropsychological deficits, therefore remain elusive (but see below).…”
Section: The Pfc Hypothesissupporting
confidence: 88%
See 1 more Smart Citation
“…The predominantly negative findings on tests of the PFC hypothesis are consistent with other research showing only subtle anatomical differences between the frontal lobes of individuals with autism compared with controls (Filipek, 1999); and also with research indicating that some but by no means all executive functions are impaired, at least in people with HFA (Hughes, 2001). The neuropsychological origins of the impaired creativity/behavioural flexibility, which is diagnostic of autism, and the neuropathology underlying the critical neuropsychological deficits, therefore remain elusive (but see below).…”
Section: The Pfc Hypothesissupporting
confidence: 88%
“…Furthermore, functional neuroimaging suggests that PFC abnormalities occur in people with autism during tasks involving theory of mind (Baron-Cohen et al, 1999;Happe  et al, 1996;Ohnishi et al, 2000). Until recently, however, there was little if any secure evidence of structural abnormalities of PFC in autism (Filipek, 1999). This situation is currently changing, with recent reports of abnormalities at the cellular level affecting both the structure and the physiology (Chugani et al, 1997;Murphy et al, 2002) of frontal lobe neurons.…”
mentioning
confidence: 99%
“…Similarly, Rourke (1995) suggested that difficulty was present in the right-hemispheric white matter in NLD. Differences have also been found in the smaller volume of the corpus callosum for children with AS despite control for white matter volume (Chung, Dalton, Alexander, & Davidson, 2004), higher volumes of white matter (Filipek, 1999), and increased volume in the caudate regions (Sears et al, 1999). While the emerging MRI research in AS suggests white matter involvement in the disorder, the findings are not conclusive.…”
Section: Cognitive Differencesmentioning
confidence: 97%
“…Castellanos et al (2002) also noted not only reduced white matter in childhood AD/ HD, but reduced cerebral grey matter in frontal and temporal cortices that was correlated with the severity of psychopathology. Filipek (1999) noted that the involvement of right frontal regions in particular seemed to depend on comorbid problems. Indeed, a recent MRI study of adolescents with conduct disorder (independent of substance-abuse) showed volumetric reductions in the right hemisphere, reminiscent of AD/HD studies (Kruesi et al, 2004).…”
Section: Structure and Functionmentioning
confidence: 99%